Using the webquest model as alternative assessment in the course LM-1001 Integrated English I at the University of Costa Rica - Navas Brenes, César Alberto (InterSedes, 2013)
This article explores the pedagogical principles as well as the advantages and recommendations of designing and implementing WebQuests in the course LM-1001 Integrated English I in the School of Modern Languages at the University of Costa Rica. This type of Web-based task was used as alternative assessment rather than traditional evaluation. This study also presents three sample WebQuests which were implemented with four groups in four different semesters of first-year students during their computer lab sessions.